First symptoms in multiple system atrophy - McKay, Jake H.; Cheshire, William P. (Clinical autonomic research, 2018)
Purpose The initial symptoms of multiple system atrophy (MSA) and, in particular, early autonomic symptoms, have received less attention than motor symptoms. Whereas pathognomonic motor signs are essential to diagnostic specificity, early symptoms important to recognition of a neurodegenerative disorder may be less apparent or diagnostically ambiguous. This observational study sought to identify the very earliest symptoms in the natural history of MSA. Methods Detailed clinical histories focusing on early symptoms were obtained from 30 subjects recently diagnosed with MSA. Historical data were correlated with neurological examinations and laboratory autonomic testing. Results Subjects’ mean age was 63.9 years. Ten were classified as having MSA-P and 20 MSA-C. The evaluations occurred 2.9 ± 0.4 months after diagnosis. The first symptom of MSA was autonomic in 22 (73%) and motor in 3 (10%) subjects ( p < 0.0001). The most frequent first symptom was erectile failure, which occurred in all men beginning 4.2 ± 2.6 years prior to diagnosis. After erectile failure, postural lightheadness or fatigue following exercise, urinary urgency or hesitancy, and violent dream enactment behavior consistent with REM behavioral sleep disorder were the most frequent initial symptoms. Neither the order of symptom progression, which was highly variable, nor autonomic severity scores differentiated between MSA-P and MSA-C. Conclusions The first symptoms of MSA are frequently autonomic and may predate recognition of motor manifestations. Orthostatic hypotension and, in men, erectile failure are among the first symptoms that, when evaluated in the context of associated clinical findings, may facilitate accurate and earlier diagnosis.